MicroRNA deregulation in keloids: an opportunity for clinical intervention?. (21st October 2015) - Yu, Xin; Li, Zheng; Chan, Matthew T. V.; Wu, William K. K.
Abstract: Keloids are defined as benign dermal scars invading adjacent healthy tissue, characterized by aberrant fibroblast dynamics and overproduction of extracellular matrix. However, the aetiology and molecular mechanism of keloid production remain poorly understood. Recent discoveries have shed new light on the involvement of a class of non‐coding RNAs known as microRNAs (miRNA), in keloid formation. A number of miRNAs have differential expression in keloid tissues and keloid‐derived fibroblasts. These miRNAs have been characterized as novel regulators of cellular processes pertinent to wound healing, including extracellular matrix deposition and fibroblast proliferation. Delineating the functional significance of miRNA deregulation may help us better understand pathogenesis of keloids, and promote development of miRNA‐directed therapeutics against this condition.